2017
DOI: 10.3389/fphar.2017.00027
|View full text |Cite
|
Sign up to set email alerts
|

Drug Utilization on Neonatal Wards: A Systematic Review of Observational Studies

Abstract: Despite limited evidence on safety and efficacy of drug use in neonates, drugs are extensively used in this age group. However, the availability of information on drug consumption in neonates, especially inpatient neonates, is limited. This paper systematically reviews published studies on drug utilization in hospitalized neonates. A systematic literature review was carried out to identify observational studies published from inception of databases used till August 2016. Four search engines, namely Medline, CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 40 publications
(76 reference statements)
2
33
2
Order By: Relevance
“…In children, drug use collectively is much more common than is usually appreciated; our work among a cohort of a million Canadian children demonstrated that children receive on average 4 prescriptions a year, confirmed by subsequent studies including a recent study revealing that American children receive on average 3.5 prescriptions a year . Within this population are 2 distinct groups; most children receive no or 1 prescription a year, but children with complex and often chronic problems—approximately 20% of children—receive 70% of all prescription drugs . Thus it is not surprising that, in the latter group of children, ADRs would be expected to be both common and important problems .…”
Section: The Burden Of Adverse Drug Reactions and Optimal Care For Chsupporting
confidence: 56%
See 3 more Smart Citations
“…In children, drug use collectively is much more common than is usually appreciated; our work among a cohort of a million Canadian children demonstrated that children receive on average 4 prescriptions a year, confirmed by subsequent studies including a recent study revealing that American children receive on average 3.5 prescriptions a year . Within this population are 2 distinct groups; most children receive no or 1 prescription a year, but children with complex and often chronic problems—approximately 20% of children—receive 70% of all prescription drugs . Thus it is not surprising that, in the latter group of children, ADRs would be expected to be both common and important problems .…”
Section: The Burden Of Adverse Drug Reactions and Optimal Care For Chsupporting
confidence: 56%
“…Far and away the largest amount of literature in this area is dominated by studies in adult medicine. Pharmacotherapy in adults is distinctly different from that in children in both the type and amount of medications used . One of the single best predictors for drug use in adults is age; the older the patient, the more medications she/he is likely to take, with more than 90% of people over age 65 being on at least 1 medication .…”
Section: The Burden Of Adverse Drug Reactions and Optimal Care For Chmentioning
confidence: 99%
See 2 more Smart Citations
“…Broad‐spectrum antibiotics (AB) is the most frequently prescribed drug type in neonates . Besides obvious beneficial short‐term effects, there is mounting evidence of negative long‐term side effects of antibiotics.…”
Section: Introductionmentioning
confidence: 99%